Analysis of Market Volatility and Economic Factors in Emerging Markets - Odhiambo, June (International Journal of Modern Risk Management, 2023)
Purpose: The aim of the study was to investigate analysis of market volatility and economic factors in emerging markets. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Findings indicated that economic indicators played a significant role in influencing market volatility, with higher inflation rates and currency fluctuations contributing to increased market uncertainty. These empirical observations provided valuable insights for investors, policymakers, and financial institutions to navigate the complexities of emerging markets and make informed decisions. Unique Contribution to Theory, Practice and Policy: Efficient Market Hypothesis Theory, Portfolio and Financial Contagion Theory may be used to anchor future studies on analysis of market volatility and economic factors in emerging markets. Stakeholder should translate theoretical insights into practical tools, researchers can contribute to informed decision-making, risk management, and market stability. Researchers should collaborate with governmental and international organizations to identify regulatory gaps and propose measures to enhance market resilience.